Update on the Natural Course of Fistulizing Perianal Crohn's Disease in a Population-Based Cohort. Issue 6 (19th October 2018) - Park, Sang Hyoung; Aniwan, Satimai; Scott Harmsen, W; Tremaine, William J; Lightner, Amy L; Faubion, William A; Loftus, Edward V
Abstract: Background: This study sought to re-estimate the cumulative incidence of perianal or rectovaginal fistulas and the associated proctectomy rate in the prebiologic era vs the biologic era using a population-based cohort of Crohn's disease (CD) patients. Methods: The medical records of 414 residents of Olmsted County, Minnesota, who were diagnosed with CD between 1970 and 2010 were reviewed. The cumulative incidence of perianal or rectovaginal fistulas from time of CD diagnosis and the cumulative rate of proctectomy from date of first perianal or rectovaginal fistula diagnosis were estimated using the Kaplan-Meier method. Results: Eighty-five patients (20.5%) diagnosed with CD between 1970 and 2010 had at least 1 perianal or rectovaginal fistula episode between January 1, 1970, and June 30, 2016. The cumulative incidence of perianal or rectovaginal fistulas was 18% after 10 years, 23% after 20 years, and 24% after 30–40 years from CD diagnosis. The cumulative incidence of perianal or rectovaginal fistulas was significantly lower in patients diagnosed in 1998 or after than in patients diagnosed before 1998 ( P = 0.03, log-rank). Among 85 patients developing perianal or rectovaginal fistulas, 16 patients (18.8%) underwent proctectomy for the treatment of perianal or rectovaginal fistulas during follow-up. Conclusions: In a population-based inception cohort of CD, one-fifth of patients were diagnosed with at least 1 perianal or rectovaginal fistula. The cumulative probability of perianal or rectovaginal fistulizing disease has decreased over time. Video Abstract: